Synthesis of Benzofurans and Indoles from Terminal Alkynes and Iodoaromatics Catalyzed by Recyclable Palladium Nanoparticles Immobilized on Siliceous Mesocellular Foam. Issue 52 (21st August 2017) - Bruneau, Alexandre; Gustafson, Karl P. J.; Yuan, Ning; Tai, Cheuk‐Wai; Persson, Ingmar; Zou, Xiaodong; Bäckvall, Jan‐E.
Abstract: Herein, we report on the utilization of a heterogeneous catalyst, consisting of Pd nanoparticles supported on a siliceous mesocellular foam (Pd 0 ‐AmP‐MCF), for the synthesis of heterocycles. Reaction of o ‐iodophenols and protected o ‐iodoanilines with acetylenes in the presence of a Pd nanocatalyst produced 2‐substituted benzofurans and indoles, respectively. In general, the catalytic protocol afforded the desired products in good to excellent yields under mild reaction conditions without the addition of ligands. Moreover, the structure of the reported Pd nanocatalyst was further elucidated with extended X‐ray absorption fine‐structure spectroscopy, and it was proven that the catalyst could be recycled multiple times without significant loss of activity. Abstract : Pd nanoparticles supported on siliceous mesocellular foam (Pd 0 ‐AmP‐MCF) were found to efficiently catalyze the reaction of o ‐iodophenols and protected o ‐iodoanilines with acetylenes to produce 2‐substituted benzofurans and indoles, respectively. In general, the catalytic protocol afforded the desired products in good to excellent yields under mild reaction conditions without the addition of ligands.